Antimicrobial resistance and its genetic determinants in aeromonads isolated in ornamental (koi) carp (Cyprinus carpio koi) and common carp (Cyprinus carpio) - Cízek, Alois; Dolejská, Monika; Sochorová, Radana; Strachotová, Katerina; Piacková, Veronika; Veselý, Tomás (Veterinary microbiology, 2010)
The aim of this study was to evaluate antimicrobial susceptibility of Aeromonas spp. isolates from common carp and koi carp coming from randomly chosen farms. The isolates were tested for susceptibility to 8 antimicrobial agents using the standard agar dilution susceptibility test. In all isolates, PCR was used to detect the presence of tet(A-E) genes, integrase genes, and gene cassettes. From the total 72 isolates of motile aeromonads sampled from koi carp, 36 isolates (50%) were resistant to oxytetracycline, 18 (25%) to ciprofloxacin, 5 (7%) to chloramphenicol, 5 (7%) to florfenicol, and 11 (15%) to trimethoprim. Among 49 isolates of motile aeromonads collected from common carp, 20 (41%) were resistant to oxytetracycline, 3 (6%) to chloramphenicol, and 3 (6%) to florfenicol. The resistance of aeromonads isolated from koi carp was significantly higher to ciprofloxacin (P=0.00024). The presence of class 1 integrons was detected in these isolates only (P=0.00024). Tet genes were detected in 40% (48/121) of isolates, with tet(E) being the most dominant. Our results demonstrated a significant difference in the incidence of resistant isolates collected from koi carp and common carp (P=0.00042). This difference can be ascribed to a distinct antibiotic policy established on consumer fish farms versus ornamental fish farms. The potential risk for resistant bacteria to spread and transmit infection to humans should be considered in cases of technological crossover between the two types of fish farms.
Keywords: Animals; Gram-Negative Bacterial Infections; mikrobiální testy citlivosti; bakteriální proteiny; kapři; integrony; Bacterial Proteins; nemoci ryb; gramnegativní bakteriální infekce; Fish Diseases; Anti-Bacterial Agents; bakteriální léková rezistence; Microbial Sensitivity Tests; Carps; zvířata; Integrons; antibakteriální látky; Aeromonas; Drug Resistance, Bacterial